2009
DOI: 10.1093/ndt/gfp102
|View full text |Cite
|
Sign up to set email alerts
|

Free and total plasma malondialdehyde in chronic renal insufficiency and in dialysis patients

Abstract: Free and bMDA concentrations identified different MDA patterns. Bound MDA, not excreted by kidneys, accounts alone for high tMDA concentrations in ESRD patients, while both fMDA and bMDA contribute to tMDA values in dialysis patients. These findings show that increased tMDA could be indicative not only of recent lipid peroxidation, and they also highlight the importance of evaluating free, bound and total MDA in patients with reduced renal function in order to assess their oxidative status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 34 publications
0
32
0
2
Order By: Relevance
“…Almost all studies to date investigated total MDA levels in CKD and dialysis patients. On the other hand, De Vecchi et al 30 studied free and bound MDA levels as well as total levels in CKD, HD, PD patients, and normal controls. They found that total and bound MDA concentrations were significantly higher in patients than in controls (ESRD>HD>PD) and free MDA levels were similar in HD and PD patients and significantly higher than CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies to date investigated total MDA levels in CKD and dialysis patients. On the other hand, De Vecchi et al 30 studied free and bound MDA levels as well as total levels in CKD, HD, PD patients, and normal controls. They found that total and bound MDA concentrations were significantly higher in patients than in controls (ESRD>HD>PD) and free MDA levels were similar in HD and PD patients and significantly higher than CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, results from previous clinical studies [26,[28][29][30], have been collected and statistically compared for the first time, with the aim to search for the best marker and/or assay and to verify their performance in evidencing oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers of oxidative stress and inflammation are usually elevated in CKD [1]. Malondialdehyde (MDA) is one of the biomarkers of oxidative stress generated from lipid peroxidation and is elevated in dialysis patients [8]. Interleukin-6 (IL-6) levels are increased in CKD and dialysis patients and correlate with the long-term outcome of chronic dialysis patients [9].…”
Section: Introductionmentioning
confidence: 99%